Damage Monitoring and Analysis of the Structure Effect on Strength of Composite Laminates. (11th October 2015) - Chiang, Chia-Chin; Tsai, Liren; Thuyet, Vu Van
Abstract : Carbon fiber reinforced polymer (CFRP) composite materials have been widely used in industries in recent years. The design of composite structures, and open-holes for joining are also widely used. Understanding of open-hole behavior is very necessary for the design of complex structures. In this paper, the initial damage, progressive damage analysis, and the effect of structure on strength of composite laminates are investigated. Based on Hashin's criteria, three-dimensional model of composite laminates containing a central open-hole is developed. The model is conducted by finite element analysis, commercial Abaqus software to simulate the whole process of initial damage, propagation of damage, and analysis of the effect of a few structures on strength of composite laminates containing open-hole.